Long‐coronavirus disease among people living with HIV in western India: An observational study. Issue 3 (2nd June 2021) - Pujari, Sanjay; Gaikwad, Sunil; Chitalikar, Abhishek; Dabhade, Digamber; Joshi, Kedar; Bele, Vivek
Abstract: Background: Long‐COVID is emerging as a significant problem among individuals who recovered from COVID‐19. Scant information is available on the prevalence, characteristics, and risk factors for long‐COVID among people living with HIV (PLHIV). Setting: A tertiary level, private, HIV clinic in western India. Methods: A prospective, observational study was conducted to assess the prevalence of long‐COVID among PLHIV. Long‐COVID was defined as the presence of at least one symptom after 30 days of illness onset. A questionnaire for assessing general, cardiorespiratory, neuro‐psychiatric, and gastro‐intestinal symptoms was used to screen individuals with history of confirmed COVID‐19. Data on demographics, HIV‐related variables, comorbidities, and severity of COVID‐19 were abstracted from electronic medical records. Univariate and multivariate logistic regression were used to identify risk factors for long‐COVID. Results: Ninety‐four PLHIV were screened for long‐COVID. Median (interquartile range [IQR]) age was 51 (47–56) years and 73.4% were males. The majority (76.6%) had a history of asymptomatic–mild COVID‐19 illness. The prevalence of long‐COVID was 43.6% (95% confidence interval [CI], 33.4–54.2). Moderate–severe COVID‐19 illness was significantly associated with long‐COVID (adjusted odds ratio, 4.7; 95% CI, 1.4–17.9; p = .016). Among individuals with long‐COVID, cough (22.3%) and fatigue (19.1%) were the commonest symptoms. The median (IQR) duration for resolution of symptoms was 15 (7–30) days. Ten individuals (10.6%) had persistent symptoms at a median of 109 days since the onset of COVID‐19. Conclusion: Long‐COVID is common among PLHIV with moderate–severe acute COVID‐19 illness. There is a need for integration of long‐COVID diagnosis and care services within antiretroviral therapy clinics for PLHIV with COVID‐19. Abstract : Long‐COVID‐19 was documented among 43.6% of people living with HIV in western India. Moderate/severe COVID‐19 illness was independently associated with long COVID‐19 in this cohort.